2018
DOI: 10.1590/0102-672020180001e1349
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Quality of Life and Body Image of Candidates to Bariatric Surgery

Abstract: Background: Physical activity enhances quality of life and body image in obese. Behavioural changes are useful tools to increase life conditions of this population. Aim: To evaluate the physical activity level of candidates to bariatric surgery and its relation with quality of life and body image, when patients are encouraged weekly by personal trainers. ) Method: This is a prospective, interventional and longitudinal study with quantitative analysis. Patients were divided into two groups, control (n=28) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…The physical dimension revealed that women with obesity present a higher degree of physical pain (P = .007), which directly interfered with their ability to perform ordinary activities. 26 Similarly, it was also observed that they felt less energy to perform these activities (P = .0009) when compared to women of G1. These findings are supported by previous studies, which highlighted that patients undergoing bariatric surgery have an improvement in physical dimension after at least 6 months of the surgical procedure.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The physical dimension revealed that women with obesity present a higher degree of physical pain (P = .007), which directly interfered with their ability to perform ordinary activities. 26 Similarly, it was also observed that they felt less energy to perform these activities (P = .0009) when compared to women of G1. These findings are supported by previous studies, which highlighted that patients undergoing bariatric surgery have an improvement in physical dimension after at least 6 months of the surgical procedure.…”
Section: Discussionmentioning
confidence: 80%
“…Assessing the quality of life ensured a holistic approach to the patients in this study, elucidating the determinants of health and the social context in which they lived. The physical dimension revealed that women with obesity present a higher degree of physical pain ( P = .007), which directly interfered with their ability to perform ordinary activities 26 . Similarly, it was also observed that they felt less energy to perform these activities ( P = .0009) when compared to women of G1.…”
Section: Discussionmentioning
confidence: 92%
“…Os resultados desta revisão apontam que as transformações positivas na vida dos participantes associaram-se a cirurgia e a modificação nos hábitos de vida. Estudo desenvolvido com candidatos a cirurgia bariátrica que foram acompanhados por educadores físicos, identificou mudança nos hábitos de vida com consequente redução na percepção de dor e na melhora da qualidade de vida (Barreto et al, 2018). Research, Society and Development, v. 10, n. 3, e31410313329, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i3.13329…”
Section: Discussionunclassified
“…Os dois resultados significativos encontrados no grupo de indivíduos ativos referem-se ao IMC na influência negativa das QVF e QVP e podem estar relacionados com a dificuldade do indivíduo obeso nas atividades físicas diárias realizadas e em sua autoimagem 27,80 .…”
Section: Tempounclassified